GAMBARAN PERSEPSI KONSUMEN TERHADAP PRODUCT QUALITY SEBAGAI PERTIMBANGAN MEMBELI PRODUK - Yohan Chowindra; Siti Rahayu; Antonius Budhiman Setyawan (Perpustakaan Universitas Surabaya, 2018)
This study aims to determine and analyze the image of consumer perceptions of Product Quality as a consideration in buying the product. The analysis is based on 9 dimensions of Performance, Features, Confromance, Durability, Reliability, Serviceability, Aesthetic, Perceived Quality and especially observe the effect of Environmental Friendly dimension to perception and consumer consideration in buying product.Data processing was conducted using IBM SPSS Statistics 18. The sampling technique that used is non-probability sampling with Convenience Sampling type. The number of sample in this research is 154. The results of this study indicate the perception of the majority of respondents of each characteristic that considers the dimensions of the quality of Environmental Friendly products (environmentally friendly). Most of the respondents had an awareness of environmental concerns that were being applied by starting to consider using environmentally friendly products. But that does not mean the other eight dimensions are not considered, but the product with the Environmental Friendly quality dimension gets a special value for the respondent's perception when considering buying a product.